2014
DOI: 10.1002/btpr.1920
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ambient light on monoclonal antibody product quality during small‐scale mammalian cell culture process in clear glass bioreactors

Abstract: During a small-scale cell culture process producing a monoclonal antibody, a larger than expected difference was observed in the charge variants profile of the harvested cell culture fluid (HCCF) between the 2 L and larger scales (e.g., 400 L and 12 kL). Small-scale studies performed at the 2 L scale consistently showed an increase in acidic species when compared with the material made at larger scale. Since the 2 L bioreactors were made of clear transparent glass while the larger scale reactors are made of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…The majority of cell lines evaluated showed higher acidic variants in BR. Deamidation is a common acidic variant that can increase with extracellular incubation during cell culture . Because of shorter residence time in TS, deamidation was less prevalent at this scale, also confirmed by our preliminary characterization of acidic fractions in mAb B anion exchange chromatography (Figure C, characterization results not shown).…”
Section: Resultssupporting
confidence: 72%
“…The majority of cell lines evaluated showed higher acidic variants in BR. Deamidation is a common acidic variant that can increase with extracellular incubation during cell culture . Because of shorter residence time in TS, deamidation was less prevalent at this scale, also confirmed by our preliminary characterization of acidic fractions in mAb B anion exchange chromatography (Figure C, characterization results not shown).…”
Section: Resultssupporting
confidence: 72%
“…In our opinion, the impact of CDM preparation parameters on process robustness is a rather neglected and thus far not well‐understood topic in therapeutic protein production. However, when considering the impact of CDM on cell growth, productivity and protein quality, it becomes obvious that monitoring of media components is advantageous . So far, media makeup is defined by strict standard operating procedures with narrow operating ranges.…”
Section: Resultsmentioning
confidence: 99%
“…21 Recent research also demonstrated that exposing mAbs to light during their production process clearly alters the charge variants profile of the final product. 22 There is therefore extensive evidence that photodegradation leads primarily to chemical changes in single amino acids of proteins and that trp, tyr, phe, and cys are the primary targets of photodegradation. In addition, photodegradation can also promote multiple cross-linking reactions due to dityrosine or disulfide formation and to noncovalent aggregation.…”
Section: Introductionmentioning
confidence: 99%